2022
DOI: 10.17235/reed.2022.8384/2021
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome before liver transplantation: does it have an impact on post liver transplantation outcomes?

Abstract: Introduction: Metabolic syndrome (MS) and cardiovascular risk factors are commonin liver transplant (LT) candidates and recipients. Cardiovascular events and de novo tumours are increasingly common causes of mortality in liver transplant recipients. The aim of this study is (i) to assess the prevalence of MS in LT recipients and its growth over the years and (ii) if the presence of MS pre-LT is associated with a higher risk of post-LT cardiovascular events (CVE), de novo tumours or early and late survival. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Of the 15 included cohort studies, majority were retrospective (n = 14) and there was one prospective study. The studies were conducted in various countries including 4 in Italy, [30][31][32][33] 3 in Spain, [34][35][36] and one in the United States, [37] Australia, [38] Belgium, [39] Singapore, [40] China, [41] Israel, [42] Germany, [5] and India, [43] respectively. A total of 2683 LT recipients were included in this study, with 740 patients developing de novo PTMS.…”
Section: Summary Of Included Articlesmentioning
confidence: 99%
“…Of the 15 included cohort studies, majority were retrospective (n = 14) and there was one prospective study. The studies were conducted in various countries including 4 in Italy, [30][31][32][33] 3 in Spain, [34][35][36] and one in the United States, [37] Australia, [38] Belgium, [39] Singapore, [40] China, [41] Israel, [42] Germany, [5] and India, [43] respectively. A total of 2683 LT recipients were included in this study, with 740 patients developing de novo PTMS.…”
Section: Summary Of Included Articlesmentioning
confidence: 99%
“…There is a paucity of scientific reports that provide evidence on the influence of new-onset MS on mid- and long-term prognoses in liver recipients. Those that exist suggest increased cardiovascular (CV) morbidity with no implications for survival rates and risk of de novo tumours [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…SIRS has a precise clinical definition, which has been validated in large patient populations ( 15 – 17 ). In this context, it has been shown by several studies that patients with MetS and/or SIRS experience higher rates of morbidity, increased instances of postoperative morbidity including cardiovascular complications, and slower recovery of function across both cardiac and non-cardiac surgery ( 18 20 ). Last but not least, frailty assessment has acquired increasing importance in recent years and it has been demonstrated that this vulnerable profile predisposes elderly patients to a worse outcome after surgery ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%